Probing the Interstellar Medium from Scintillation of the Swooshing Pulsar B0919+06 - Z. Wang; Z. G. Wen; J. P. Yuan; N. Wang; Z. Wang; J. L. Chen; H. G. Wang; W. Han; H. Wang; X. F. Duan; C. B. Lyu; J. P. Wang; et al. (The Astrophysical Journal, 2024)
Radio observations of pulsars offer a potential method to probe the intricate microstructure in the turbulent interstellar medium. Here we report on a high-resolution dynamic spectral analysis of the “swooshing pulsar” B0919+06 observed with the Five-hundred-meter Aperture Spherical radio Telescope over multiple epochs and with the ultrawideband receiver on the Parkes radio telescope. For all observations, the dynamic scintillation spectra, two-dimensional autocovariance functions, and secondary spectra are presented. At 1250 MHz, the decorrelation bandwidth, diffraction timescale, and the drift rate are determined to be Δ ν _d = 25.89 ± 7.55 MHz, ${\rm{Δ }}{τ }_{d}=14.42± 3.98$ minutes, and ${dt}/dν =0.07± 0.14\,minutes$ MHz ^−1 , respectively. The frequency dependencies of the scintillation parameters exhibit single power-law spectral behaviors, indicating that the electron density fluctuations in the interstellar medium approximately follow the Kolmogorov spectrum. The secondary spectra exhibit two distinct parabolic arcs with well-determined curvatures of 0.002 and 0.02 s ^3 for the outer and inner arcs, respectively. The locations of the scattering screens are approximately determined to be 157.3 and 726.0 pc, respectively, from the pulsar for isotropic scattering. The inner scintillation arc is present contemporaneously over a wide frequency range, indicating that the scintillation arc is a broadband phenomenon. The arc curvature scales with observing frequency as a power law with an index of −2.05 ± 0.05, which implies that the scattering screen spans a physical distance from 689.7 to 883.3 pc from the pulsar.